Sequencing Groebke–Blackburn–Bienaymé and Aza-Michael Addition Reactions: A Modular Strategy for Accessing a Diverse Collection of Constrained Benzoxazepine and Imidazopyrazine Systems - Srinivasulu, Vunnam; Al-Marzooq, Farah; Hamad, Mohamad; Khanfar, Monther A.; Ramanathan, Mani; Soares, Nelson C.; Al-Tel, Taleb H. (Synthesis, 2021)
We present a divergent strategy that permits access to diversely functionalized benzoxazepinium scaffolds fused to various heterocycles. The described strategy features a one-pot combination of the Groebke–Blackburn–Bienaymé reaction and an aza-Michael addition. Methyl (E)-4-(2-formylphenoxy)but-2-enoate and its derivatives are utilized as central elements in this cascade. These building blocks are reacted with a variety of functionalized amino-azines and tert-butyl isocyanide under ytterbium triflate [Yb(OTf)3] catalysis. The ensuing cascade represents a rapid, modular and atom-economic process that leads to the construction of a diverse collection of constrained benzoxazepinium systems from a wide substrate scope.
Keywords: aza-Michael addition; benzoxazepines; indolopyrazines; diversity-oriented synthesis; multicomponent reactions; Groebke–Blackburn–Bienaymé; modular synthesis